The Effectiveness Of The Sharia-Based Transaction Payment System In Increasing The Trust Of Pilgrims In The Umrah Travel Service Of Pt. Zam Zam Islamic Tourism - Maharani, Annisa; Isra Hayati (Al Tijarah, 2024)
In the current era of globalization, the religious tourism industry, especially in Umrah pilgrimage trips, is experiencing very rapid growth. Customer trust in travel services is one of the main factors that determine the success of a travel company in maintaining and expanding its market share in the midst of competition. The implementation of this sharia-based payment system can increase pilgrims' trust in the services provided by Umrah travel agencies. This study aims to find out how effective the sharia-based transaction payment system is in increasing pilgrims' trust in Umrah travel services at PT. Zam Zam Islamic Tourism. This research was conducted on PT. Zam Zam Wisata Islami which is located on Al Falah street, Muctar Basri No. B6, Kel, Glugur Darat 2, Kec. The approach used in this study is a qualitative approach.  The data analysis technique used through data collection uses an interview process, data reduction, and drawing conclusions.  This study shows that the sharia-based transaction payment system has a significant influence on the trust of pilgrims. The implementation of this system has proven to be effective in increasing the trust of pilgrims. However, there are several challenges in its implementation, such as the lack of understanding of pilgrims about the payment system carried out in sharia and the competitiveness of other travel parties. Based on the analysis, it can be concluded that, with the existence of a sharia-based payment system at PT. Zam Zam Wisata Islami has an important role in building the trust of pilgrims, therefore, the company needs to optimize and educate the pilgrims and improve Islamic financial services, this needs to be done to increase the effectiveness of this system in the future.